Evaluasi Kualitas Hidup Pasien Kanker Payudara Pengguna Kemoterapi di RSUD Provinsi NTB - Baiq Lenysia Puspita Anjani; Cyntiya Rahmawati; Nursela Hijriani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Functional status changes may occur as side effects of chemotherapy in cancer patients, potentially reducing their quality of life. This study aimed to evaluate the quality of life of chemotherapy patients at the West Nusa Tenggara Provincial Hospital. An analytical observational method with a cross-sectional approach was used. Subjects were breast cancer patients aged ≥18 years undergoing chemotherapy. Quality of life was assessed using the FACT-G questionnaire, while demographic data and chemotherapy regimens were obtained from medical records. Data analysis included correlation tests for demographic variables and independent T-tests to compare quality of life scores across chemotherapy regimens. Results showed no significant correlation between chemotherapy regimens (TAC and AC) and variables such as age, treatment duration, occupation, education, or cancer stage (P>0.05). However, the number of treatment cycles was significantly correlated with the chemotherapy regimen (P<0.05). Patients receiving the AC regimen had higher average scores in social, emotional, and functional dimensions compared to those receiving TAC. In conclusion, there was no statistically significant difference in quality of life between the TAC and AC groups (P>0.05), though overall FACT-G scores indicated a better quality of life in patients treated with the AC regimen.